2022
DOI: 10.1002/smtd.202101545
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Triboelectric Series Using Gradient Positive and Negative Charge‐Confinement Layer with Different Particle Sizes of Mesoporous Carbon Materials

Abstract: As a method to maximize the energy efficiency of triboelectric nanogenerators (TENGs), high‐voltage charge injection (HVCI) on the surface is a simple and effective method for increasing surface charge densities. In this study, positive and negative triboelectric series are controlled using a 3‐layer gradient charge‐confinement wherein the particle sizes of the mesoporous carbon spheres (mCSs) are sequentially arranged depending on the external surface area of the mCSs. In the gradient charge‐confinement layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Interestingly, the added MMT helps enhance the triboelectric properties of the polymer matrix, which can be exploited to facilitate a constant buildup of electrons on the fibrous matrix and enhance the filtration efficiency. In this regard, many studies have reported the improvement in the adsorption efficiency of ultrafine dust particles through electrostatic attraction, particularly by using the electrostatic charge on the surface generated by friction between two materials (i.e., triboelectricity). Similarly, for the polymer–MMT membrane, the stresses exacted on the membrane by constant airflow should be able to provide triboelectricity, constantly supplying the filter membrane with extra surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the added MMT helps enhance the triboelectric properties of the polymer matrix, which can be exploited to facilitate a constant buildup of electrons on the fibrous matrix and enhance the filtration efficiency. In this regard, many studies have reported the improvement in the adsorption efficiency of ultrafine dust particles through electrostatic attraction, particularly by using the electrostatic charge on the surface generated by friction between two materials (i.e., triboelectricity). Similarly, for the polymer–MMT membrane, the stresses exacted on the membrane by constant airflow should be able to provide triboelectricity, constantly supplying the filter membrane with extra surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…[76] In addition, some structures may facilitate capture the charge dissipated from the triboelectric material to the electrode if used for intermediate layers of TENGs, which is also called charge trapping and storage layer. [77][78][79][80][81][82] This section presents the design of different structures of electrospun porous materials for TENGs to enhance their electrical properties and obtain mechanical properties, directionality, and air permeability for TENGs. Further, we complement the approach on doping nanomaterials for electrical performance enhancement and functional expansion of TENGs such as mechanical property.…”
Section: Types Of Electrospun Triboelectric Materialsmentioning
confidence: 99%
“…[138] Therefore, the microspheres at present are basically used as filler materials compounded with other structures. [81,137] With the improvement of mechanical properties of microspheres, it will be possible to develop pure microspheres as triboelectric materials. For electrospun honeycomb-based microspheres, the tough preparation process has limited their application in TENG to some extent.…”
Section: Characteristics and Properties Of Electrospun Microspheresmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increase of PO 4 3− concentration, the removal of F − by C-SAA decreased to 94.45%, 91.77%, 87.13%, 83.06%, 81.44 and 81.38%, respectively, while the removal of F − by C-SAAoa decreased to 98.87%, 91.31%, 87.68%, 84.60%, 83.31 and 83.27%, respectively. This phenomenon is mainly due to the high density of negative charge of PO 4 3− (Cha et al, 2022), resulting in its easy adsorption on the surface of positively charged materials. PO 4 3− (3/3.40) and F − (1/ 1.33) possess similar charge radii.…”
Section: Effect Of Coexisting Anionsmentioning
confidence: 99%